1996
DOI: 10.1097/00005373-199603001-00044
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and Mechanism of Traumatic Amputation by Explosive Blast

Abstract: The mechanism of traumatic amputation of limbs by explosion is presented. A survey of blast casualties from Northern Ireland revealed that amputations through joints were very uncommon--the principal site was through the shaft of the long bones. Computer modelling of a bone exposed to blast forces reinforced the hypothesis developed from the casualty survey, that the primary mechanism of the bone injury was the direct coupling of the blast wave into the tissues. The fracture occurs from the resulting axial str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(65 citation statements)
references
References 3 publications
2
60
1
Order By: Relevance
“…Five were military personnel (83%) and one was a civilian. Median Injury Severity Score (ISS) for survivors was 5 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), and the ISS for the deceased was 63 (38-73), with a significant difference between groups, p<0.001.…”
Section: Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Five were military personnel (83%) and one was a civilian. Median Injury Severity Score (ISS) for survivors was 5 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), and the ISS for the deceased was 63 (38-73), with a significant difference between groups, p<0.001.…”
Section: Mortalitymentioning
confidence: 99%
“…All of these injuries can compromise the musculoskeletal system. Hull, et al studied the mechanism of limb amputations after explosive blasts 5 . Of 100 cases with lethal injuries reviewed, 34 had limb amputation.…”
Section: Introductionmentioning
confidence: 99%
“…This results in soft tissue injury and bone micro-fractures. Hull (1995) demonstrated that a goat limb, 1 shielded from the effects of the detonation products and fragments, could be fractured by the blast wave alone when placed in close proximity to the seat of the explosion. Using a finite element modelling technique, he predicted that the blast wave will have reached the limb prior to any displacement of the limb from the detonation products.…”
Section: Primary Orthopaedic Blast Injurymentioning
confidence: 99%
“…Due to the bone geometry and the differential movement allowed by the knee and ankle joint, the bending forces exerted on the tibia by the blast wave, results in an area of stress concentration. The peak hoop and axial stresses within this area exceeds the tensile failure stress of bone, resulting in fracture; adapted from Hull (1995). (b) A traumatic amputation of the femur.…”
Section: Secondary Orthopaedic Blast Injurymentioning
confidence: 99%
“…Primary blast injury is the result of blast wave overpressure and affects the air or fluid filled organs. Experimental work links primary blast injury with skeletal trauma to the ribs and traumatic amputations [8,11,12]. Secondary blast injury represents injuries caused by the fragmentation of munitions and the impact of these fragments on the human body.…”
Section: Introductionmentioning
confidence: 99%